Blue-green infrastructure and the intermediate scale - Manuela Guzmán (Dearq, 2022)
This article presents three case studies of urban projects (Urbanización Can Cortada in Spain; Maiporé in Colombia, and Água Carioca in Brazil) built between 2008 and 2017. These are evaluated according to the compliance regarding three pillars of water-sensitive cities: 1) design strategies to manage water, 2) the project’s capacity to provide ecosystem services, and 3) community involvement in the design, implementation, and maintenance processes. The projects propose an alternative vision for water management and investigate new design paradigms capable of reducing the impact of urbanisation on the water cycle.